Viable Sweetpotato Techologies in Africa for Northern Mozambique - International Potato Center (2016)
We established multiplication sites with 52 individual decentralized vine multipliers (DVMs). Together with government extension services, we supplied 132,280kg of cuttings to 15,220 households. Since July 2015, 237.4 hectares of orange-fleshed sweetpotato have been planted. Our nutrition messages reached 7,784 households with children under five years of age.